Human paleogenetics of Europe – The known knowns and the known unknowns. Issue 79 (February 2015) - Brandt, Guido; Szécsényi-Nagy, Anna; Roth, Christina; Alt, Kurt Werner; Haak, Wolfgang
Abstract: The number of ancient human DNA studies has drastically increased in recent years. This results in a substantial record of mitochondrial sequences available from many prehistoric sites across Western Eurasia, but also growing Y-chromosome and autosomal sequence data. We review the current state of research with specific emphasis on the Holocene population events that likely have shaped the present-day genetic variation in Europe. We reconcile observations from the genetic data with hypotheses about the peopling and settlement history from anthropology and archaeology for various key regions, and also discuss the data in light of evidence from related disciplines, such as modern human genetics, climatology and linguistics.